Understanding Human Trafficking In The Perspective Of Al-Azhar Interpretation (Review Surah Yusuf [12]: 19-20) - Afrizal Nur; Sri Kurniati Yuzar; Fadhli Ananda (Jurnal Ushuluddin, 2023)
The aim of this study was to the phenomenon of human trafficking that occurred in the Prophet Yusuf and at this time. Human trafficking is a phenomenon that has occurred long before the Prophet Muhammad was born. This phenomenon has even been experienced by the Prophet Yusuf AS. The Prophet Yusuf was abandoned by his siblings, sold by travelers who found him, and made into slaves by those who bought him. There are two academic problems formulated in this study. First, how is the interpretation of QS. Yusuf [12]: 19-20 in Al-Azhar's interpretation of human trafficking. Second, how is the practice of human trafficking that occurred in the prophet Yusuf and the current era. This type of research is a qualitative research using a library research approach. The results of this study contain two main findings, namely; (1) QS. Yusuf [12] asserts about the crime of human trafficking experienced by the prophet Yusuf. In this case, Prophet Yusuf was sold by a traveler who found him in a well and then sold him at a very low price and made him a slave. (2) The practice of human trafficking that occurred in the prophet Yusuf and the present era has almost the same form. If the prophet Yusuf was treated like a slave, traded and so on, then in the present era such crimes still occur. Tuti Tursilawati as a migrant worker from Indonesia who worked in Saudi Arabia also received cruel treatment from her employer. Tuti was forced to work hard and was not paid, and she was often sexually harassed. Actions like this are a form of trafficking crime in the current era. Keyword: Human Trafficking, Prophet Yusuf, Slavery, QS. Yusuf [12]: 19-20, Tafsir Al-Azhar